POTASSIUM RESERVES MOBILIZATION IN CALCAREOUS SOIL NORTHN IRAQ BY USING CONTINUES CUTTING OF ALFALFA CROP (NTU Journal of Agriculture and Veterinary Science, 2025)
A field experiment was conducted in the Al-Jawsaq area (Mosul city ), using the local alfalfa crop (Medicago sativa L)  as a plant indicator, to monitor the release indogentic potassium, during  24 successive cuts biological indictors(green fodder, dry yield, and total potassium uptake ) were described according to the kinetic approach by using the equations, (zero order, first order, second order, diffusion, Elovich, and power function). The results showed that the continuation of the processes of Successful mowing without potassium fertilization led to the depletion of the soluble and available forms, thus relying on the supply of potassium from the unprepared form. The results also indicated a significant variation in the values of green fodder yield, dry matter, and total potassium absorption, with a superiority for the power function equation, which obtained the highest coefficient determinant and a standard error compared to the rest equation. The equations are the biological absorption rate coefficient from the latent soil storage (0.9405), the rate coefficient of dry matter production (0.9377), and the rate coefficient of green fodder production (0.9081). The path of the biosorption process according to kinetic principles revealed the existence of two paths, the first with a high release rate (the phase available) and the second with a low release rate (non-available). The results also showed the superiority of the role of non-available potassium over both soluble and available potassium, which indicates the role of stored potassium in supplying the plant with potassium during the renewed growth stages after each mowing.